Effects of Methamphetamine on Single Unit Activity in Rat Medial Prefrontal Cortex In Vivo. (23rd August 2007) - Jang, Jinhwa; Ha, Hee-Jin; Kim, Yun Bok; Chung, Young-Ki; Jung, Min Whan
Abstract : To investigate how neuronal activity in the prefrontal cortex changes in an animal model of schizophrenia, we recorded single unit activity in the medial prefrontal cortex of urethane-anesthetized and awake rats following methamphetamine (MA) administration. Systemic MA injection (4 mg/kg, IP) induced inconsistent changes, that is, both enhancement and reduction, in unit discharge rate, with a subset of neurons transiently (< 30 min) elevating their activities. The direction of firing rate change was poorly predicted by the mean firing rate or the degree of burst firing during the baseline period. Also, simultaneously recorded units showed opposite directions of firing rate change, indicating that recording location is a poor predictor of the direction of firing rate change. These results raise the possibility that systemic MA injection induces random bidirectional changes in prefrontal cortical unit activity, which may underlie some of MA-induced psychotic symptoms.